EFEK HEPATOPROTEKTOR DARI EKSTRAK ETANOL DAUN JOHAR (Cassia siamea LAMK.) PADA TIKUS (Rattus norvegicus) - Safriani Rahman; Rachmat Kosman; Andi Cassia Siamea (Fakultas Farmasi UMI, 2017)
Johar leaf has been empirically used as malaria and hepatitis medicine. This research aims to determine hepatoprotective effect of ethanol extract of Johar leaves (Cassia siamea Lamk.) of rats liver. This research used 15 tested rats divided into 5 groups, group I was given Na.CMC 1% (negative control), group II ethanolic extract of Johar leaves of 50 mg/kgBB, group III ethanolic extract of Johar leaves of 250 mg/kgBB, group IV ethanolic extract of Johar leaves of 500 mg/kgBB, and group V as a comparison given suspension curliv® of 42,86 mg/kgBB. Giving suspension curliv® was orally done once a day for 7 days. On the 8th day, the experimental rats were given paracetamol suspension dosage of 2,5 g/kgBB. Measurements of SGPT content was done before therapy (normal), after therapy, and after administration of paracetamol. The results showed that the ethanolic extract of Johar leaves with the dose of 50; 250; 500 mg/kgBB have a hepatoprotective effect and dose is 500 mg/kgBB which was not statistically significantly different from curliv®.